2017
DOI: 10.1140/epjc/s10052-017-5268-9
|View full text |Cite
|
Sign up to set email alerts
|

Fate of an accretion disc around a black hole when both the viscosity and dark energy is in effect

Abstract: This paper deals with the viscous accretion flow of a modified Chaplygin gas towards a black hole as the central gravitating object. A modified Chaplygin gas is a particular type of dark energy model which mimics of radiation era to phantom era depending on the different values of its parameters. We compare the dark energy accretion with the flow of adiabatic gas. An accretion disc flowing around a black hole is an example of a transonic flow. To construct the model, we consider three components of the Navier-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…It is followed from the reference [30] that viscous Chaplygin gas accretion increases the strength of outflowing wind and decreases the effective disc length as we increase the viscosity. This says that the feeding up property of accretion disc is negatively working if DE of modified Chaplygin gas type is accreting.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…It is followed from the reference [30] that viscous Chaplygin gas accretion increases the strength of outflowing wind and decreases the effective disc length as we increase the viscosity. This says that the feeding up property of accretion disc is negatively working if DE of modified Chaplygin gas type is accreting.…”
mentioning
confidence: 92%
“…The lower bound of the ratio η s surprisingly decrease beyond universal lower bound. In some recent articles [30,31] authors have shown that DE catalyze the effect of viscosity in the accretion disk as DE exerts negative pressure. So from the Eq.…”
mentioning
confidence: 99%
“…Bulk viscosity takes larger value than shear viscosity. These ideas lead the authors to study the viscous DE accretion and the lower limit of the shear viscosity to entropy density ratio [40]. All these works have chosen the central compact object to be a Kerr BH.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the wind branch's density is very high near to the BH. Recently, Dutta, S. and Biswas, R. [24] have shown that, if the viscosity is encountered, the wind branch achieves speed equal to that of light at a distance which is lesser than the nonviscous case. Again BH spin enhances this tendency.…”
Section: Introductionmentioning
confidence: 99%